2010 IEEE Global Telecommunications Conference GLOBECOM 2010 2010
DOI: 10.1109/glocom.2010.5683232
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Assisted Single-Copy Routing in Underwater Delay Tolerant Networks

Abstract: Abstract-One challenge in delay tolerant networks (DTNs) is efficient routing, as the lack of contemporaneous end-to-end paths makes conventional routing schemes inapplicable. Many existing DTN routing protocols adopt multi-copy replication and/or are incognizant of mobility models. Hence they are not suitable for networks with extremely stringent resources and time-varying mobility models such as underwater sensor networks. In this paper, we propose a generic prediction assisted single-copy routing (PASR) sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Simulation results showed that this approach can provide differentiated packet delivery according to application requirements and can achieve a good e2e performance tradeoff among delivery ratio, average e2e delay, and energy consumption. A Prediction Assisted Single-copy Routing (PASR) scheme that can be instantiated for different mobility models is proposed in [14]. An effective greedy algorithm is adopted to capture the features of network mobility patterns and to provide guidance on how to use historical information.…”
Section: Related Workmentioning
confidence: 99%
“…Simulation results showed that this approach can provide differentiated packet delivery according to application requirements and can achieve a good e2e performance tradeoff among delivery ratio, average e2e delay, and energy consumption. A Prediction Assisted Single-copy Routing (PASR) scheme that can be instantiated for different mobility models is proposed in [14]. An effective greedy algorithm is adopted to capture the features of network mobility patterns and to provide guidance on how to use historical information.…”
Section: Related Workmentioning
confidence: 99%
“…3 we plot minimal MDT and ADD for a set of packets generated at bus 3029 and destined to bus 3038 at different time instants of the day. Due to the piece-wise linear property of these metrics in terms of packet generation time 6 , we only need to use our MDT-routing algorithm on a finite number of generation time instants. As expected, the MDT exhibits a step-curve: later packet generation does not affect the MDT until a critical contact is lost and the routing has to change leading to a later delivery.…”
Section: Simulation Studiesmentioning
confidence: 99%
“…in deterministic DTNs. While such assumption is realistic in some specific scenarios like interplanetary networks [3] or transport networks [2], these works have also a theoretical interest, because they shed light on the fundamental hardness of the problem [1], and on best case performances [17], [4], and can be used in the learning phase of a practical scheme [6]. This paper falls within the second category and studies the packet routing problem in deterministic DTNs.…”
mentioning
confidence: 99%
“…According to the number of replicas, these policies can be divided into two classes: that is, single-copy and multi-copy. In the first class, nodes keep only one copy of the message and attempt to forward that copy towards the node which has higher probability to meet the destination, such as the works in [6], [7], etc. Therefore,…”
Section: Introductionmentioning
confidence: 99%